Securitization and optimal foreclosure - Kuong, John Chi-Fong; Zeng, Jing (Journal of Financial Intermediation, 2021)
Does securitization distort the foreclosure decisions of non-performing mortgages? In a model of mortgage-backed securitization with an endogenous foreclosure policy, we find that the securitizing bank adopts a tougher foreclosure policy than the first-best, despite resulting in higher loan losses. This is optimal because foreclosure mitigates the adverse selection problem in securitization by making the optimal security, a risky debt, less information-sensitive. We further show that policies that limit mortgage foreclosure would discourage the bank’s ex ante screening effort, reducing the quality of securitized mortgages. Our model yields novel testable predictions on the effect of mortgage securitization on foreclosure rates, loan performance, and mortgage servicing.